Expression patterns of Wnt genes in the venom claws of centipedes. Issue 5 (20th September 2013) - Hayden, Luke; Arthur, Wallace
SUMMARY The venom claws of centipedes, also known as forcipules, represent an evolutionary novelty that must have arisen in the centipede stem species, as they are not found in any other myriapods. The developmental‐genetic changes that are involved in the origin of novelties are of considerable interest. It has previously been shown that centipede forcipules have a unique Hox code. However, this is a combinatorial code: no single Hox gene has a forcipule‐specific expression. Here, we focus on Wnt genes. Two genes of this family show forcipule‐specific expression in the "model centipede" Strigamia maritima: Wnt7 and Wnt11. For Wnt7, this forcipular expression zone seems to be a new one, which has arisen in evolution subsequently to other expression zones of the same gene. However, for Wnt11, the forcipule‐specific expression probably arose by reduction of a more general pattern that originally included most or all of the limbs of an ancestral myriapod. Thus the developmental‐genetic basis of the evolutionary change that turned the first pair of walking legs into venom claws is complex, involving different types of change in expression pattern. This sort of complexity is likely to be the case regarding evolutionary changes in morphology in general. Whether the origins of those features that can be considered as novelties are different in terms of their developmental‐genetic basis from more routine evolutionary changes remains an open question.